La educación para la paz exige un cambio de modelo de paz: desaprendiendo la exclusividad de la Pax para unirla a la Eirene y la noviolencia (2016)
Learning for peace implies that people that go into the process is not the same people as before. This is because they might have unlearned violent behavior and have got other pacifists behaviors. Understanding that human beings are not instinctive as animals that always respond to stimulus. Human beings have the freedom to delay the normal answer, invent another one or not respond at all. It has to do with a change of personality, characterized by opening to each other, where they now maintain even relations though they have different way of thinking.The peace learning means to recognize that during the first years of post-conflict many things would not change. The Colombian army will not disappear, assuring the forever roman concept of Pax. The Colombian State will continue being neo liberal, maintaining the globalization that day by day produces social inequality. The time of peace does not take people to submission but the outreach of the greek concept of peace Eirene. This will make citizens the possibility of making claims to the state, well thought and without violence.